Use of systemic corticosteroids for atopic dermatitis: International Eczema Council consensus statement. (1st March 2018) - Drucker, A.M.; Eyerich, K.; de Bruin‐Weller, M.S.; Thyssen, J.P.; Spuls, P.I.; Irvine, A.D.; Girolomoni, G.; Dhar, S.; Flohr, C.; Murrell, D.F.; Paller, A.S.; Guttman‐Yassky, E.
Summary: Atopic dermatitis, commonly called eczema, is an itchy skin disease that affects 7% of children and 10% of adults in the US. When it is severe, it is often difficult to treat. Corticosteroids, such as prednisone, are a class of medications that in their oral form (e.g., pills) are generally recommended against in guidelines for physicians. This is in contrast to topical steroids (e.g., creams and ointments) which are the recommended first line treatment for atopic dermatitis. Even though they are not recommended in most cases, many patients with severe atopic dermatitis are prescribed systemic corticosteroids. Many of these prescriptions may be inappropriate because of the side effects of these medications and because once the medications are stopped, the skin disease often flares badly. The goal of our study was to reach agreement among experts in treating atopic dermatitis on when and how systemic corticosteroids can be used for atopic dermatitis. Sixty International Eczema Council members from 20 countries participated in our survey and agreed on 12 statements. Agreement was reached that systemic corticosteroids should generally be avoided but can be used rarely for severe atopic dermatitis under certain circumstances, including a lack of other treatment options, as a bridge to other systemic therapies or phototherapy, during flares in need of immediate relief, in anticipation of a major life event such as a wedding or in the most severe cases. Respondents agreed that if used, treatment should be limited to short‐term. We hope our paper will be of use to dermatologists, allergists, pediatricians, primary care doctors and any other healthcare providers who treat patients with atopic dermatitis. Hopefully it will lead to decreased inappropriate use of systemic steroids and better outcomes for patients with atopic dermatitis.